A new safflower variety- parbhani suverna (pbns-154) resistant to biotic stress released for Maharashtra state: A new safflower variety- parbhani suverna (pbns-154) resistant to biotic stress released for Maharashtra state - S B GHUGE; S A SHINDE; C V AMBADKAR; V M PANCHAL (Journal of Oilseeds Research, 2023)
A new safflower variety Parbhani Suverna (PBNS-154) was evaluated in IET and RMT at different research station of VNMKV, Parbhani under rainfed and irrigated conditions during 2016-2021 for seed and oil yield as well as reaction to biotic stresses viz; Alternaria leaf spot, Fusarium wilt and aphid pest in comparison with the checks PBNS-12 and sharada. It has recorded 23.62 and 27.69% higher seed yield over the checks PBNS-12 and sharada, respectively. This variety was found tolerant to Fusarium wilt and Alternaria leaf spot disease reaction and also moderately resistant to aphid pest as compared with all other qualifying varieties and checks. Hence, the variety PBNS -154 is released for cultivation in Safflower growing areas of Maharashtra.